2 D Hybrid of Ni‐LDH Chips on Carbon Nanosheets as Cathode of Zinc–Air Battery for Electrocatalytic Conversion of O2 into H2O2. Issue 6 (4th November 2019) - Huang, Junheng; Chen, Junxiang; Fu, Changle; Cai, Pingwei; Li, Yan; Cao, Linlin; Liu, Wei; Yu, Peng; Wei, Shiqiang; Wen, Zhenhai; Li, Jinghong
Abstract: It remains great challenge to develop precious‐metal‐free electrocatalysts to implement high‐activity electrochemical conversion of O2 into value‐added hydroperoxide species (HO2 − ), which are vulnerable when exposed to various transition‐metal‐based catalysts. A strategy based on steric hindrance and layered nickel‐based layered double hydroxide (Ni‐LDH) induction has been developed for one‐pot inlaying high‐density ultrathin 2 D Ni‐LDH chips on in situ‐grown carbon nanosheets (Ni‐LDH C/CNSs). The resulting material exhibits high electrocatalytic selectivity with a faradaic efficiency up to 95 % for oxygen reduction into peroxide and attains a fairly high mass activity of approximately 22.2 A g −1, outperforming most metal‐based catalysts reported previously. Systematic studies demonstrate that the greatly increased defect concentration at Ni edge sites of Ni‐LDH chips results in more active sites, which contributes a favorable thermodynamically neutral adsorption of OOH* and adsorbed H2 O2 molecules relatively weakly. Additionally, the modified CNSs effectively suppress H2 O2 decomposition and avoid O−O bond cleavage to produce H2 O by steric effects. The synergistic effect of CNSs and Ni‐LDH chips therefore leads to high activity and high selectivity in a two‐electron pathway. A proof‐of‐concept zinc–air fuel cell is proposed and set up to demonstrate the feasibility of green synthesis of peroxide, generating an impressive H2 O2 production rate of 5239.67 mmol h −1  gcat. −1 . Abstract : Hydrogen peroxide production : A one‐pot strategy is developed for inlaying high‐density ultrathin nickel‐based layered double hydroxide (Ni‐LDH) chips on in situ‐grown carbon nanosheets to form a hybrid material. Benefiting from the synergistic effect of nanosheets and Ni‐LDH chips, the 2 D hybrid shows high selectivity toward H2 O2 production and an impressive H2 O2 production rate as cathode of a zinc–air battery.